Pengenalan Hukum Pidana Tentang Tindak Kekerasan Kepada Pelajar Sekolah Menengah Pertama (SMP) Dan Sekolah Menegah Atas (SMA) Di Kota Cilegon - Fuqoha Fuqoha; Fitria Agustin (Pusat Studi Sosial dan Pengabdian Masyarakat Fisipkum Universitas Serang Raya, 2020)
The introduction of law for community is held with aim to sharing knowledge and understanding of law. The target of the law introduction activities are junior high school (SMP) and senior high school (SMA) with based on data and fact about violence between students in schools. With sharing knowledge activities is hoped to through law introduction will be able to increase the sense of tudents responsibility and avoid the violent behaviour among the students. The method of implementing activities uses the participatory learning and action model by interactive discussions with students. From a series activities carried out gives the result with a very high about acts of violence by students. With a purposive sampling method give the result of questionnaire showed 55% of students had been victims of violence and 77% of students has seen violent behaviour in others. Therefore, the introduction of law will continue to be carried out to increase knowledge and understanding of law among the students.